2015
DOI: 10.1093/ejo/cjv051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skeletal maturity using maxillary canine, mandibular second and third molar calcification stages

Abstract: The calcification stages of UC, LM2, and LM3 as indicators of skeletal maturity could be clinically used with caution, until this method is verified with a larger sample group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Interestingly, third molars are unique teeth, as their eruption time may vary from 17 to 24 years, depending on the ethnographic region and race 1 . Recently, discussions regarding the influence of the third molars on dentition have become highly important from several aspects, including their development, formation and retention and their effect on teeth crowding 2 – 4 . Consequently, understanding of the regulatory mechanisms of third molar development variability is of great clinical importance for making decisions on the timing of third molar surgical removal, autologous transplantation, orthodontic treatment planning and chronological age estimation for medico-legal purposes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, third molars are unique teeth, as their eruption time may vary from 17 to 24 years, depending on the ethnographic region and race 1 . Recently, discussions regarding the influence of the third molars on dentition have become highly important from several aspects, including their development, formation and retention and their effect on teeth crowding 2 – 4 . Consequently, understanding of the regulatory mechanisms of third molar development variability is of great clinical importance for making decisions on the timing of third molar surgical removal, autologous transplantation, orthodontic treatment planning and chronological age estimation for medico-legal purposes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Different parameters are used to describe pubertal growth in children. Some of the parameters that are used in determining pubertal growth spurt by assessing growth and development in adolescence are chronological age, pubic hair appearance in males and females, menstruation onset in females, radiographic evaluation of bone maturation stages and evaluation of tooth calcification stages [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…This may a have a negative impact on the proper development of dental occlusion, as well as other consequences, such as an imbalance in the stomatognathic system. 1,23 This study found a high prevalence of agenesis of the third molar (20.71%) in the studied population. This figure is high in comparison to other studies conducted in the population of Venezuela, where agenesis of this tooth was observed in 8.7% of the total number of radiographies studied.…”
Section: Resultsmentioning
confidence: 58%